2018
DOI: 10.2147/ceor.s157306
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent pneumatic compression is a cost-effective method of orthopedic postsurgical venous thromboembolism prophylaxis

Abstract: BackgroundVenous thromboembolism (VTE) is a major complication after lower-limb arthroplasty that increases costs and reduces patient’s quality of life. Using anticoagulants for 10–35 days following arthroplasty is the standard prophylaxis, but its cost-effectiveness after accounting for bleeding complications remains unproven.MethodsA comprehensive, clinical model of VTE was created using the incidences, clinical effects (including bleeding), and costs of VTE and prophylaxis from randomized controlled trials,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 49 publications
0
12
0
Order By: Relevance
“…A previously published cost-utility model specific to hip and knee arthroplasty was extended to consider short-term (1 year) health and economic outcomes associated with all the major available types of prophylaxis [17]. The published semi-Markov model was informed by a structured literature review to identify data related to THA and TKA, secondary outcomes and prophylaxis regimens.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A previously published cost-utility model specific to hip and knee arthroplasty was extended to consider short-term (1 year) health and economic outcomes associated with all the major available types of prophylaxis [17]. The published semi-Markov model was informed by a structured literature review to identify data related to THA and TKA, secondary outcomes and prophylaxis regimens.…”
Section: Methodsmentioning
confidence: 99%
“…The published semi-Markov model was informed by a structured literature review to identify data related to THA and TKA, secondary outcomes and prophylaxis regimens. The following secondary safety outcomes were identified and accounted for pulmonary embolism (PE), DVT, post-thrombotic syndrome (PTS), heparin-induced thrombocytopenia (HIT), major and minor bleeding and intracranial haemorrhage (ICH) [17]. All patients started in post-surgical ‘No VTE’ state and received prophylaxis for 30 days.…”
Section: Methodsmentioning
confidence: 99%
“…28 In addition, the sequential compressions device customizes the compression cycle time by sensing the venous filling time and this may allow more venous compressions than the single-compartment device (which has a fixed cycling time of one minute) over the same period of time. Although IPC has a reasonably strong evidence base in reducing DVT and PE in a variety of hospitalised patients−either alone or in combination with anticoagulant prophylaxis−especially for patients at high risk of VTE, 15,16,37,38 there is no high-level RCT evidence to suggest that a sequential compressions IPC device is more efficacious than a single-compartment device in reducing DVT/PE. 39 Because StO 2 in the lower limbs had previously been demonstrated to correlate positively with regional blood flow measured by an ultrasound Doppler, 34 our results provide some rationale to support testing the hypothesis that a sequential compressions mode IPC is better than a single-compartment mode IPC in improving venous leg ulcers healing in patients with chronic leg ulcers 40 and reducing lower limb DVT.…”
Section: Discussionmentioning
confidence: 99%
“…Additional considerations when interpreting findings concerning VTE chemoprophylaxis dosing are the use intermittent pneumatic compression therapy systems, as well as postoperative time to ambulation. Several studies have indicated the benefit of implementing intermittent pneumatic compression (IPCs) as a standard for VTE mechanical prophylaxis, and as such, can be a confounding factor that reduces incidence of VTE [44,45] . Likewise, a decrease in time to ambulation postoperatively has been shown to decrease incidence of VTE [46] .…”
Section: Discussionmentioning
confidence: 99%